Evaluation of sagittal changes in Class II Div 2 patients with decelerating phase of growth by PowerScope appliance: A retrospective cephalometric investigation - Gowri Sankar Singaraju; Venkataramana Vannala; Srikanth A Ankisetti; Prasad Mandava; Vivek Reddy Ganugapanta; Deepthi Unnam (Wolters Kluwer Medknow Publications, 2019)
Background: Restricted mandibular growth is observed in Class II Div 2 malocclusions. The fixed functional appliances are used to effect the skeletal changes in patients with end stages of skeletal maturity. Aim: This cephalometric study aimed to distinguish the skeletal and dental corrections done in the mandible on skeletal Class II Div 2 subjects when treated with PowerScope appliance (American Orthodontics, Sheboygan, WI). Materials and Methods: This is a cephalometric study based on the retrospective data. The patients selected for this study were with Class II Div 2 malocclusion and assessed to be in decelerating phase of skeletal growth. A total of 12 patients were selected after applying inclusion and exclusion criteria. A PowerScope was placed after incisor correction and followed up till Class I molar relation was achieved. The initial values (T1) at the time of placement of the appliance and the final values at the end of the molar correction (T2) were noted. The cephalometric parameters at T1 and T2 were assessed using sagittal occlusal (SO) analysis by Pancherz. The paired Student's t-test was used to analyze pre- and posttreatment changes. Results: There was sufficient lengthening of the mandible (4.38mm). Both the dental and skeletal alterations were observed in the mandible. These changes were marked compared to the maxilla. The pre- and posttreatment changes were statistically significant for the mandibular skeletal changes (P < 0.001) as well as mandibular incisor proclination (P < 0.001). Conclusion: The PowerScope can be used as a propeller for sagittal mandibular correction in Class II Div 2 patients.